The role of job analysis in improving the job rotation process - a field study in the technical institutes at Tishreen University - حسن لينا سمير; ديب كندة علي; فياض لينا (Latakia University Journal - Economic and Legal Sciences Series, 2022)
This research aimed to study the relationship between Job Analysis and Job Rotation in technical institutions at Teshreen University, The researcher studied the job analysis through its five dimensions (job duties, responsibilities, job human requirements, job environment, job relations, and job equipment) ,While the dependent variable (job rotation) was addressed as a one-dimension. The study relied on the descriptive approach in the research; it also relied on the method of statistical analysis of the initial data that had been collected by Questionnaire, which had been distributed among /221/ employees in the administrative offices of the technical institutions, at University. The data had been analyzed relying on one sample t test and person coefficient (correlation) by using SPSS /20/. The research concluded a set of results, the most important ones are: The lowest of reliance on the job rotation process in technical institutes. There is a strong significant relationship between defining duties and job rotation in the studied environment. There is a medium-strength significant relationship between defining job equipment and human requirements on one hand, and job rotation on the other. There is a weak significant relationship between the environment and the job relations on one hand, and job rotation on the other.